Legal Protection of Notaries Who Are Suspected (Study of Decision N0.17/PID. PRA/2022/PN. Mdn) - Hoiriyah, Hoiriyah (International Significance of Notary, 2023)
Abstract: Legal protection  for notaries who are indicated criminal  acts  in connection with the authentic deed they make.  Public prosecutors and   judges generally apply certain articles in the Criminal Code (KUHP)  to drag notaries into criminal cases because Law Number 2 of 2014 concerning Notary Positions (UUJN) does not contain concepts  and systems at all   Notary criminal liability. The notary office  is a public office because notaries are  appointed and dismissed by the government. Notaries perform state  duties  and the deed they make, namely minuta (original deed), is a state document. In Indonesia, a notary is referred to as a General Officer because he is numbered and dismissed by the  general power (government) and  is given the authority and  obligation to serve the public in certain matters, and therefore he participates in exercising  the authority  of  the government. conclusion that legal protection of Notaries is dalam carrying out the  duties of  his office as a General Officer can be seen in several instruments that reflect notary privileges, including the right of  denial, the  obligation of denial and the  right of exclusivity when summoned for questioning  information by investigators,  public prosecutors or judges, which must be with the  approval of the Regional Notary Honor Council. Keywords: Legal protection, Notary, Criminal act, Authentic deed, Legal consequences